OCORRÃŠNCIA DO NEMATÃ“IDE ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜¤ð˜°ð˜§ð˜§ð˜¦ð˜ªð˜¤ð˜°ð˜ð˜¢ Lordello & Zamith, 1960, EM LAVOURA DE CAFÃ‰ NO SUL DO ESTADO DE MINAS GERAIS - Guerra Filho, Evaristo Gomes; Dâ€™Antonio, Ãlvaro Machado; Almeida, Saulo Roque de; Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2020)
OCORRÃŠNCIA DO NEMATÃ“IDE ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜¤ð˜°ð˜§ð˜§ð˜¦ð˜ªð˜¤ð˜°ð˜ð˜¢ Lordello & Zamith, 1960, EM LAVOURA DE CAFÃ‰ NO SUL DO ESTADO DE MINAS GERAIS